2012
DOI: 10.1242/jeb.064030
|View full text |Cite
|
Sign up to set email alerts
|

Growth and innate immunity are not limited by selection for high egg testosterone content in Japanese quail

Abstract: SUMMARYThe effects of maternal androgens on fitness-related traits of offspring are generally assumed to be epigenetic adaptations to the environment that may be encountered by the next generation. Possible constraints of high yolk androgen transfer are still not understood, although a suppressed immune response in offspring is frequently considered. The aim of our study was to examine the innate immune defence in high (HET) and low egg testosterone (LET) lines of Japanese quail, which differ in the hormonal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Differences in body mass in favour of HET as compared to LET quail were discernible at the end of the second week after hatching and were similar to the growth rates that we recorded in our previous studies (Okuliarova et al, 2011a;Kankova et al, 2012). The data also indicate that the different growth rate between lines persists under mild food shortage and is not present only under optimal food conditions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Differences in body mass in favour of HET as compared to LET quail were discernible at the end of the second week after hatching and were similar to the growth rates that we recorded in our previous studies (Okuliarova et al, 2011a;Kankova et al, 2012). The data also indicate that the different growth rate between lines persists under mild food shortage and is not present only under optimal food conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Dried blood smears were fixated and stained with May-Grünwald and Giemsa-Romanowsky solutions (Kankova et al, 2012). Final differential count of white blood cells (WBC) was determined as percentages of heterophils (He), lymphocytes (Ly), eosinophils, monocytes and basophils per 200 leukocytes on each slide.…”
Section: Heterophil/lymphocyte Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…In precocial birds, experimental in ovo injection of T resulted in significant effects on physiology (Cucco et al, 2008) and on the behavioural phenotype of young chicks (Daisley et al, 2005;Okuliarova et al, 2007;Bertin et al, 2008). Moreover, our previous experiments showed that the selection for high egg T content positively affected post-hatching growth (Okuliarova et al, 2011b), whereas elevated growth rate was not compromised by a weaker innate immune response in the HET as compared with the LET quail chicks (Kankova et al, 2012). Therefore, the increase of yolk T concentrations in the second laying cycle in the HET females may reflect an improvement of their breeding value between cycles that together with the better prospects of experienced females to cope with a stable environment can increase their reproductive success.…”
Section: Discussionmentioning
confidence: 98%